(untitled) (Contextus - Revista Contemporânea de Economia e Gestão, 2025)
Contextualization: Religion and concerns about financial resources have accompanied humanity from its earliest days to the present. In Christianity, discussions arise about how religious doctrines can influence the behavior of believers. In this context, it is relevant to understand how Christians (both Catholics and Protestants) manage financial matters in their daily lives. Objective: This study aims to examine how religion influences the financial behaviors of its followers. Method: A quantitative approach was adopted, applying 513 questionnaires (268 Catholics and 245 Protestants) containing 29 items rated on a 0-to-10 agreement scale, which were grouped into eight constructs. The study employed Exploratory Factor Analysis (EFA), Ordinary Least Squares (OLS), and Generalized Linear Models (GLM) as estimation methods. Results: The findings indicate that religion influences aspects such as financial education, monitoring, overconfidence, saving behavior, conscious spending, risk tolerance, and financial planning. Differences between Catholics and Protestants were observed only in monitoring and risk tolerance. Conclusions: This study contributes to financial education practices grounded in ethical and religious principles while also informing public policies and financial products tailored to different beliefs.